ANALISIS PEMANFAATAN MEDIA WORDWALL TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI KELAS IV SDN KARANGREJO 03 - Nur Afifatur Rohmah; Mely Agustin Reni Pitasari; Muhammad Ilyas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the use of Wordwall media in Mathematics learning and students' learning interest on the material of picture patterns and number patterns in grade IV of SDN Karangrejo 03. This type of research is descriptive qualitative with the research subjects of grade IV teachers and 28 students. Data were collected through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the use of Wordwall media in Mathematics learning is able to create a fun, interactive learning atmosphere and foster student enthusiasm. Students appear more active, confident, and brave in answering questions. Teachers also assess Wordwall effectively helps students understand the concept of picture patterns and number patterns visually and concretely. Thus, the use of Wordwall media improves students' interest in learning mathematics in elementary school.